2015
DOI: 10.1016/j.jss.2014.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Expression of indocyanine green-related transporters in hepatocellular carcinoma

Abstract: The intratumoral expression of MDR3, a key efflux transporter of ICG, affected the prognosis of patients with HCC, presumably by altering the lipid composition of the lipid bilayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
1
34
1
Order By: Relevance
“…One of ICG's applications in the clinic is to serve as a preoperative evaluator of liver function by intravenous injection prior to hepatectomy, with the dye being accumulated in hepatocellular carcinoma (HCC) tissue. 53 The ICG in combination with NIFR imaging of HCC has been developed for intraoperative navigation during open surgery and laparoscopic surgery. 54,55 But it is known that ICG can make normal tissues emit fluorescence signals with high intensity during some surgical procedures, such as partial nephrectomy, 56 which is similar to the observations made in ICG-receiving (i.v.…”
Section: Clinical Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…One of ICG's applications in the clinic is to serve as a preoperative evaluator of liver function by intravenous injection prior to hepatectomy, with the dye being accumulated in hepatocellular carcinoma (HCC) tissue. 53 The ICG in combination with NIFR imaging of HCC has been developed for intraoperative navigation during open surgery and laparoscopic surgery. 54,55 But it is known that ICG can make normal tissues emit fluorescence signals with high intensity during some surgical procedures, such as partial nephrectomy, 56 which is similar to the observations made in ICG-receiving (i.v.…”
Section: Clinical Experiencementioning
confidence: 99%
“…The uptake of ICG mediated by OATP1B3 and impaired biliary excretion of ICG caused by MDR3 contribute to the accumulation of ICG in HCC tissues. 53 In addition, Ishizawa et al found that the portal uptake of ICG in HCC cells is mediated by Na þ ∕taurocholate transport protein and OATP1B3 after preoperative intravenous administration. 54 Serum components, such as albumin and low-density lipoprotein (LDL), play important roles in the delivery of hydrophobic NIRF dye to cells.…”
Section: Enhanced Permeability and Retention Effectmentioning
confidence: 99%
“…As a result, complex laparoscopic work like suturing takes less time [101]. Laparoscopic liver resection can also be helped by the use of indocyanine green fluorescence, which has the advantages of real time illumination of occult lesions [103,104], revealing the surgical margins [105], identifying anatomical landmarks of the liver [106][107][108][109][110], and showing a more precise pathology in surgical specimens [111,112]. These are relatively new technologies, and it may be difficult to demonstrate a statistically significant clinical difference with their use.…”
Section: Hcc With Portal Vein Invasionmentioning
confidence: 99%
“…P-gp: P-glycoprotein; NF-κB: Nuclear factor-κB; ADM: Adriamycin. Anti-cancer drug efflux is one of the most common mechanisms of MDR of HCC cells, and it is mediated by ATP-binding cassette transporters [33,34] , such as P-gp encoded by MDR1 gene, which is located downstream of the NF-κB signaling pathway. P-gp expression regulated by MDR1 is the most important and common cause of MDR, and weakened the apoptosis of cancer cells induced by chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%